The Position of The Accounting Profession in The Realization of The 2030 Sustainable Development Goals (SGD's) - Ahmadi, Ahmadi; Nasution, Yenni Samri Juliati; Nurwani, Nurwani (International Journal of Economics Development Research (IJEDR), 2024)
This research aims to analyze the role of accountants in realizing the Sustainable Development Goals 2030 in Singkuang I Village-Owned Enterprises. The research method used is descriptive qualitative with a case study approach. Data was obtained through interviews, observation and documentation of relevant data related to the development of Sustainable Development Goals (SGD's) 2030 in Singkuang I Village-Owned Enterprises. Data was analyzed using the triangulation method between interview results, sustainability theory and role theory. The results of this research found accountants' views on the Sustainable Development Goals (SGD's) that are currently occurring. In Village-owned enterprises, the goals that can be implemented by accountants are still limited in various targets, limited information regarding Sustainable Development Goals (SGD's), lack of awareness of Sustainable Development Goals (SGD's). Development Goals (SGD's), the level of success of all Sustainable Development Goals (SGD's) related to accountants is still relatively low.